Teachers' and professors' perception of telework in Romania - Maria-Alexandra Sârbu; Cosmin-Nicolae Mirea; Mihaela Mihai; Puiu Nistoreanu; Elham Dadfar (Amfiteatru Economic Journal, 2021)
The first mentions of working from home date from 1979, the appearance of the Internet leading to an increase in the number of companies that have applied this system. Remote work, work from home, telecommuting, as well as teleworking are concepts that describe an alternative activity of performing traditional work. With the onset of the Coronavirus pandemic, the shift in a higher or lower proportion of companies' online activities, depending on the economic sector in which they operate, has become inevitable and sudden, with telework becoming the new normality among employees and employers. The objective of this study is to find out to what extent teachers in Romania agree to carry out teaching activities in the telework system and whether the educational environment (pre-university or univeristar), the degree of effort put in and the degree of fatigue felt in the telework system influence the extent to which teachers agree to carry out teaching activities in this type of system.The data was collected through a questionnaire-based exploratory research on a sample of 208 higher education professors and pre-university teachers. Non-parametric statistical methods of data analysis were used to measure the perception of study participants in the telework system and statistical methods suitable for qualitative data analysis were used for the assumptions: ordinal regression, Mann-Whitney U Test and Kruskal-Wallis Test. Research results show that teachers make an additional effort to carry out telework system activitiescompared to the teaching activity period in schools/campus'to the majority of respondents (87.5%), leading to a much higher feeling of fatigue (73.5%), and as the main impediment to online teaching, the evaluation of the progress of pupils/students. The study can support the management of Romanian education, at micro and macro level, in the correct substantiation of decisions on the sizing and evaluation of teaching activities and related processes that teachers carry out in telework conditions.
Keywords: I21; I23; J24; J81; 330; telework; teachers; online education; nonparametric statistical analysis